Endelig! Historien om en tiltrængt public service succes - Kann-Rasmussen, Nanna; Balling, Gitte (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2017)
The article discusses why and how SKAM, as a public service production, has become a success. The article presents two interconnected challenges for public service broadcasters today. The first challenge pertains to the fact that young people in particular turn away from traditional television; the second challenge relates to the concept social media logic, a logic that is largely incompatible with public service logic. The article presents a discussion on how SKAM has met these challenges. The article focusses mainly on its Danish reception. Through SKAMs thematic emphasis, the series offers its intended audience (young people) a contemporary guide to Nordic values. Furthermore, its transmedial distribution has engaged a large audience of people who are otherwise moving away from traditional public service content.